2021
DOI: 10.1007/s10750-021-04710-x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nitellopsis obtusa (Desv.) J. Groves, a regionally alien and invasive charophyte, on macrophyte diversity in the species native range

Abstract: This study aimed to determine the relationships between the abundance of Nitellopsis obtusa, a controversial charophyte, locally red-listed in its native Eurasian range but invasive in North America, and the species diversity of macrophyte stands dominated by N. obtusa. Three lakes of different morphology, productivity and catchment were surveyed in the species native range. In each lake, the species composition and cover of three N. obtusa-dominated stands were determined monthly from spring to autumn and ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…Brainard and Schulz (2017) found that native and non-native macrophyte richness declined in central New York State lakes where N. obtusa was present, and Ginn et al ( 2021) documented reduced biomass of macrophytes coinciding with the colonisation and establishment of N. obtusa in Lake Simcoe. A recent study of N. obtusa in its native range also showed a negative effect on macrophyte diversity with increasing N. obtusa dominance (Pełechaty et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Brainard and Schulz (2017) found that native and non-native macrophyte richness declined in central New York State lakes where N. obtusa was present, and Ginn et al ( 2021) documented reduced biomass of macrophytes coinciding with the colonisation and establishment of N. obtusa in Lake Simcoe. A recent study of N. obtusa in its native range also showed a negative effect on macrophyte diversity with increasing N. obtusa dominance (Pełechaty et al, 2021).…”
Section: Discussionmentioning
confidence: 90%
“…(2021) documented reduced biomass of macrophytes coinciding with the colonisation and establishment of N. obtusa in Lake Simcoe. A recent study of N. obtusa in its native range also showed a negative effect on macrophyte diversity with increasing N. obtusa dominance (Pełechaty et al., 2021). There are likely to be several mechanisms by which N. obtusa displaces other macrophyte species.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Прикладом типових місцезростань N. obtusa є великі глибокі вулканічні озера (Віко, Болсена, Браччанно, Лаціо, Немі та ін.) в Італії (Azzella, 2014), озера Балканського п-ва (глибоке Шкодра та мілководне Преспа) (Blazencic et al, 2006), Південного Уралу (Велике Міасове, Єлове) (Veisberg, Isakova, 2010), Польщі (Pelechaty et al, 2022), Литви (глибоке Дуся, мілководне заболочене Жувінтас) (Sinkeviciene, 2007), водойми в авандельті Волги (Zhuvogliad, Krivonosov, 1982) тощо. За оптимальних умов зростання вид здатен формувати довготривалі щільні моно-або маловидові зарості та конкурувати з деякими видами Charales, наприклад з C. aspera та C. contraria, і представниками судинних водних рослин (Azzella, 2014;Pelechaty et al, 2022).…”
Section: результати та обговоренняunclassified